CORROSION RATE ANALYSIS AND REMAINING LIFE ASSESSMENT OF ATMOSPHERIC HYDROCARBON STORAGE TANK IN PETROLEUM PROCESSING FACILITIES - Emirsyach Marchio Zhafiri Rahman; Rahmat Widodo; Virda Hersy Lutviana Saputri (Department of Mechanical Engineering Education, 2026)
This study was conducted to analyze the corrosion rate and Remaining Life Assessment (RLA) of an atmospheric storage tank in a petroleum processing facility using Ultrasonic Thickness Meter (UTM) measurement data. The analysis was complemented by a Root Cause Analysis (RCA) employing the Ishikawa Fishbone Diagram approach and a Risk-Based Inspection (RBI) evaluation to provide optimal inspection recommendations. Based on the calculation results, the tank has been in service since 1984; however, its structural condition remains within an acceptable and safe operating range. The RCA results indicate that corrosion on the tank shell is caused by a combination of technical and non-technical factors. The calculated risk level places the tank in the medium-risk category. Overall, the structural integrity of the tank can still be considered suitable for continued operation.